A) 4(x-3)=20
b) 6(2x+1)=3(3x-8)
c) -2(3x-1)-3=-4
d)3k-(10+k)=8
e)4+2(x-1)=6
f)5-2(y+3)=8
g)-1+4(2z-1)=3
h)2y+3(4-y)=y
i)6(3y+2)-5(4y+6)=-6
j)-7(2z-3)-5(4-3z)=1
k)0=-8(x+3)+4(2x-6)
l)3=-3(5y+2)-6(3y-7)
ł)2(7x-3)=5-4(6-4x)
m)2(9y-1)-3(2y+1)+1=5(4y+3)
n)-3-5(3x-2)=-8
o)4z-3(3z-5)=2z+1
p)8(2x-)+3(4-5x)=0
r)-4(x-2)=8-2(2x-5)
s)x-4+3(3-2x)=6(x-1)
t)3y-2[5(y-1)-4]=4(7-3y)

Potrzebne to na jutro
daje naj

2

Odpowiedzi

  • dari
  • Początkujący
2010-03-29T21:02:11+02:00
Ale co tu trzeba zrobić? Jakie jest polecenie?
4 3 4
2010-03-29T21:15:53+02:00
A) 4(x-3)=20
4x-12=20
4x=32
x=8

b) 6(2x+1)=3(3x-8)
12x+6=9x-24
3x=-30
x=-10

c) -2(3x-1)-3=-4
-6x+2-3=-4
-6x=1
x=-1/6

d)3k-(10+k)=8
3k-10-k=8
2k=2
k=1

e)4+2(x-1)=6
4+2x-2=6
2x=4
x=2

f)5-2(y+3)=8
5-2y-6=8
2y=9
y=4,5

g)-1+4(2z-1)=3
-1+8z-4=3
8z=8
z=1

h)2y+3(4-y)=y
2y+12-3y=y
-2y=-12
y=6

i)6(3y+2)-5(4y+6)=-6
18y+12-20y-30=-6
-2y=12
y=-6

j)-7(2z-3)-5(4-3z)=1
-14z+21-10+15z=1
z=-10

k)0=-8(x+3)+4(2x-6)
0=-8x-24+8x-24
0=-48 sprzeczność

l)3=-3(5y+2)-6(3y-7)
3=-15y-6-18y+42
33y=33
y=1

ł)2(7x-3)=5-4(6-4x)
14x-6=5-24+16x
-2x=13
x=-6,5

m)2(9y-1)-3(2y+1)+1=5(4y+3)
18y-2-6y-3+1=20y+15
-8y=19
y=-19/8

n)-3-5(3x-2)=-8
-3-15x+10=-8
-15x=-15
x=1

o)4z-3(3z-5)=2z+1
4z-9z+15=2z+1
-7z=-14
z=2

p)8(2x-)+3(4-5x)=0
16x+12-15x=0
x=-12

r)-4(x-2)=8-2(2x-5)
-4x+8=8-4x+10
0=10 sprzeczność

s)x-4+3(3-2x)=6(x-1)
x-4+9-6x=6x-6
-11x=-11
x=1

t)3y-2[5(y-1)-4]=4(7-3y)
3y-2(5y-5-4)=28-12y
3y-10y+10+8=28-12y
5y=10
y=2
2 5 2